Choosing offshore location in the fashion industry - Chernyayeva, Yelyzaveta; Semenenko, Vadim; Čajka, Radek, 1983-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Ukrainian fashion brands' strategic decision-making process for offshore fashion sites is examined in the thesis. Local firms are adapting and outsourcing to be competitive in the fast-changing fashion market owing to digital and geopolitical shifts. This study examines how skilled labor, cost dynamics, lead periods, political stability, and logistical efficiency affect outsourcing decisions. A qualitative examination of offshore trends and obstacles using semi-structured interviews with brand representatives and secondary data from industry papers and academic literature is provided. China's strong infrastructure and skilled labor market make it a top offshore destination. Vietnam and India are particularly important because to their logistical and economic advantages. The thesis presents a strategy framework for prudent offshore that balances economic and ethical factors. To reduce risks, it recommends varying outsourcing destinations and focusing on continual development and global flexibility. This result emphasizes the importance of outsourcing for Ukrainian brands seeking development and worldwide market penetration.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses